New Beginnings: A Pastorate Start Up Workbook - Oswald, Roy M. (Rowman & Littlefield Publishers, 1989)
Roy Oswald, who ministers to pastors with great compassion, perceptiveness, and skill, now brings eight more years of field experience to an updated edition of "New Beginnings." Important new material includes: More wisdom about how to take care of yourself in the midst of the stress of transition...how to get clear about your role in your new parish...how to get along with people you don't like (as well as people you DO like)...how to celebrate with the search committee. Getting off to a good start in your new pastorate is crucial. If you have moved or are about to move into a new parish ministry, this workbook will help you take advantage of the special opportunities and avoid the pitfalls in the first 18 months of a pastorate.